Analysis of the Emerging Market for Poultry By-Products in Ghana - Etriakor Kofi Gbordzoe; Edward Ebo Onumah; Akwasi Mensah-Bonsu (Universitas Sebelas Maret, 2024)
The paper examined the emerging poultry by-products market, delving into the nature, revenue generation, influencing factors, and constraints of the market, using data from poultry farmers, aggregators, and cattle farmers. The paper described the nature of the market using descriptive statistics and a flow chart, estimated its contribution to poultry revenue, and examined the factors influencing the proportion of revenue contributed using a Tobit model. Kendall’s coefficient of concordance was used to measure the level of agreement among the poultry farmers in ranking identified constraints. The poultry by-product market is currently characterized by only poultry droppings trading, with Côte d’Ivoire as the largest user (76% of the consumption) in cross-border informal trade and an average selling price of 8.39 USD per metric ton. The emerging market for the by-products can be described as seasonal. Annual revenue per poultry farmer for poultry droppings is 1,072.26 USD. Management type, production scale, and membership of poultry farmers’ association influenced the proportion of revenue contributed from poultry droppings. The emerging poultry droppings market provided an opportunity for small-scale farms to earn additional income and organic manure to support sustainable farming. The key constraints among the poultry farmers participating in the by-products market were low prices and a lack of processing and storage facilities. The study recommended that agriculture sector development agencies should support the development of value chains for poultry droppings and other poultry by-products to help expand the market for sustainable agriculture production under the circular economy framework.